Successful Leadership Practice in School - Koirala, Kamal Prasad (Education and Development, 2019)
This paper mainly focuses on successful leadership practices in secondary school. It aims to identify the recent models and theories of successful leadership practice in schools, and explore the experience of school principal regarding successful school leadership in the Nepalese context. A qualitative study was carried out in Gorkha district for the collection of data. A successful head teacher was selected for in-depth interview to explore the perception and experience about successful practice of school leadership. The findings of the study reveal that strong interpersonal skills, people-centered leadership, clear communication of vision and goal, focus on academic achievement, co-curricular activities, transparency, creating a positive work environment, knowledge of pedagogical contents, and cooperation and collaboration with various stakeholders are the vital constituents of successful leadership practices.